DEVELOPMENT OF ONLINE INTERACTIVE LEARNING MEDIA USING GeoGebra APPLET ON PROBABILITY - Melinda Pebrianti; Isnaini Handayani (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This study is intended to determine the feasibility of online interactive learning media using the Geogebra Applet on the probability material developed. The use of the model in this development research is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects included mathematics teachers and class VIII B students of Gema Nurani Integrated Islamic Junior High School. The data collection technique used was observation in the form of needs analysis and interviews and questionnaires. The results of the study were obtained based on the percentage of validity test scores by two expert validators including material experts and media experts as well as a questionnaire response from mathematics teachers and students to obtain the feasibility of the developed learning media. Based on the results of the assessment by the material expert validator, the percentage is 94.64% in the very appropriate category and media experts at 73.08% in the appropriate category. While the results of the feasibility of the mathematics teacher response questionnaire showed a percentage of 92.5% with a very decent category and a student response questionnaire of 88.04% with a very decent category. Thus, the use of the Geogebra Applet in the probability material is very feasible to be applied as an online interactive learning medium in class VIII.